Dissecting through barriers: A mixed‐methods study on the effect of interprofessional education in a dissection course with healthcare professional students. Issue 4 (16th January 2015) - Fernandes, Alisha Rebecca; Palombella, Andrew; Salfi, Jenn; Wainman, Bruce
<x xml:space="preserve">Abstract</x> Healthcare delivery is reliant on a team‐based approach, and interprofessional education (IPE) provides a means by which such collaboration skills can be fostered prior to entering the workplace. IPE within healthcare programs has been associated with improved collaborative behavior, patient care and satisfaction, reduced clinical error, and diminished negative professional stereotypes. An intensive interprofessional gross anatomy dissection course was created in 2009 to facilitate IPE at McMaster University. Data were collected from five cohorts over five years to determine the influence of this IPE format on the attitudes and perceptions of students towards other health professions. Each year, 28 students from the medicine, midwifery, nursing, physician's assistant, physiotherapy, and occupational therapy programs were randomly assigned into interprofessional teams for 10 weeks. Sessions involved an anatomy and scope‐of‐practice presentation, a small‐group case‐based session, and a dissection. A before/after design measured changes in attitudes and perceptions, while focus group data elaborated on the student experience with the course. Pre‐ and postmatched data revealed significant improvements in positive professional identity, competency and autonomy, role clarity and attitudes toward other health professions. Qualitative analysis of intraprofessional focus group interviews revealed meaningful improvements in a number of areas including learning anatomy, role clarity, and attitudes towards other health professions. Anat Sci Educ 8: 305–316. © 2015 American Association of Anatomists.